Re/orienting writing studies : queer methods, queer projects - Banks, William P.; Cox, Matthew B.; Dadas, Caroline (Utah State University Press, 2019)
"The intersection between queer theory and rhetoric and research methods in writing studies. Focusing theoretical attention on common research practices to demonstrate how queer rhetorics of writing/composing, textual analysis, history, assessment, and embodiment/identity significantly alter both methods and methodologies in writing studies"--Provided by publisher